Patrimônio Cultural Imaterial e educação no Cariri, Ceará, Brasil - Mourão, Lorrana Caliope Castelo Branco (2022)
ntangible Cultural Heritage (ICH) is a set of practices, representations, knowledge, instruments, and skills that communities and groups recognize as part of their heritage. The ICH is covering, inter alia, five domains, oral traditions, and expressions, including languages; traditional craftsmanship; performing arts; knowledge and practices concerning nature and the universe; and social practices, rituals, and festive events. On the whole, the 2003 Convention for the Safeguarding of the Intangible Cultural Heritage emphasizes the ICH’s safeguarding and transmission in and among States Parties (Aikawa-Faure, 2009). Article 14 of the Convention signals that ICH’s safeguarding measures must be promoted and guaranteed through education. In particular, Brazil is one of the States Parties that ratified the 2003 Convention. In northeastern Brazil, in the south of Ceara, Cariri Cearense is a region that has a very expressive Intangible Cultural Heritage (Brito, 2007). The principal objective of this study is to explore what role education plays in safeguarding the Intangible Cultural Heritage in Cariri. The secondary aim is to understand the challenges that the ICH’s transmission faces in the region and how it influences safeguarding measures. The mixed-method (nested) was used as a methodology (Creswell, 2018), in which the primary method was qualitative, through Intervention Research and Cartography (Rocha and Aguiar, 2013; Kastrup, 2009) and the secondary, quantitative (Creswell, 2018). The core empirical fieldwork was performed in a public Technical High School in Cariri and in communities linked to the ICH. The first phase of the study took place at the school through a workshop with students of a Cultural Management technical course. In the second phase, semi-structured interviews were applied to students and teachers, culture masters, managers of non-governmental organizations, and politicians. In the third phase, a questionnaire was presented to students of the school. The methodological instruments used were participant observation, a field book method, workshop, interviews, and questionnaire. The qualitative data were analyzed using the NVivo software and quantitative data from the SPSS and Iramuteq. The results were analyzed according to three spectrums: political, school, and subjective. In the political spectrum, the meager budget, the marginalization of the ICH groups, and the low participation of groups in the political decision-making process were identified as important elements that affected ICH’s transmission in formal and non9 formal education. In the school spectrum, education model, curricula, lack of continuous and systematic actions, were observed. In the subjective spectrum, the sense of belonging to the community was identified as crucial for the ICH transmission. Overall, non-governmental organizations were identified as vital allies to support cultural heritage transmission in formal and non-formal education actions. As a result, although education is essential to safeguard ICH, many challenges still need to be faced in Cariri.